Implementation of Restorative Justice in the Criminal Act of Arisan Fraud in the Perspective of Maqāṣid Al-Syarī‘Ah and Ṣulḥ: Implementasi Restorative Justice Pada Tindak Pidana Penipuan Jual-Beli Arisan dalam Perspektif Maqāṣid Al-Syarī‘Ah dan Ṣulḥ - Muhammad Alvin Nashir; Harefa, Safaruddin; Ghufron, Muhammad (Al-Jinayah : Jurnal Hukum Pidana Islam, 2025)
Restorative justice is a process of resolving criminal cases that involves the parties to restore justice, prioritizing a peaceful agreement and the fulfillment of the rights of victims and the responsibilities of perpetrators. Although it has been included in the provisions of each law enforcement agency, the implementation of restorative justice often experiences a differentiation between the requirements and the reality that occurs in the field. This attracted the author to conduct an implementation study of the restorative justice process in a case involving the fraudulent buying and selling of arisan, with a get-or-decline system handled by the Sat. Reskrim Polres Jombang. By using a type of juridical-empirical legal research method with a case approach, and a statutory approach, where the data is obtained from interviews and documents. Based on the study's results, the fraud case meets the formal and material requirements outlined in Police Regulation No. 8 of 2021, Article 4. At the level of the concept of criminal procedure law, the process of investigation, from investigation to termination of the case, has been in line with the standard operating procedures in the Criminal Procedure Code. Second, the case of fraudulent social gatherings has reflected the fulfillment of the context of maqāṣid al-syarī‘ah and the principle of ṣulḥ in efforts to resolve it according to Islamic law.